The struggle within dual systems of government: dealing with conflict between traditional leaders and ward councilors in the greater Giyani Municipality in South Africa - Muchaku, Shadreck; Magaiza, Grey (Frontiers in Political Science, 2024)
Introduction Current frameworks of conflict resolution have shown only partial success, particularly in the context of local municipalities where conflicts persist. There is a pressing need for context-specific framework that address leadership conflicts while fostering peace. Methods To address the lack of progress in resolving conflicts, this study identifies major challenges undermining the assimilation and implementation of objectively informed conflict resolution strategies. A purposive sampling method was employed to select 33 respondents from the Greater Giyani Municipality. Data were collected through semistructured interviews and analyzed using statistically established matrix scoring procedures. ATLAS.ti software was utilized for data analysis. Results Without claiming to be exhaustive, this paper highlights examples of externalities that threaten the coexistence of the dual system of governance in South African communities, with a focus on leadership conflict and unsustainable peace. Factors contributing to conflict escalation include capacity constraints, lack of inclusive, bias, divisive decision-making and contested court decisions. Discussion The study underscores the importance of addressing these challenges to foster effective conflict resolution. It emphasizes the need for the scientific community to provide critical information necessary for responding effectively to these challenges. Conclusion To enhance conflict resolution in local municipalities, it is imperative to develop context-specific frameworks that address underlying challenges and promote sustainable peace. This requires concerted efforts from both researchers and practitioners to provide the necessary insights and strategies for resolution.